Molecular epidemiology and antimicrobial resistance of Salmonella species from clinical specimens and food Items in Lebanon - Fadlallah, Sukayna M; Shehab, Marwa; Cheaito, Katia; Saleh, Majd; Ghosn, Nada; Ammar, Walid; El Hajj, Rima; Matar, Ghassan M (The Journal of Infection in Developing Countries, 2017)
Introduction: Foodborne illnesses can be due to a wide range of bacteria, one of the most common being Salmonella. In this study, PulseNet International was implemented in Lebanon to identify circulating pathogens at the species and strain levels, determine antimicrobial resistance, and link food sources and clinical cases during outbreaks. Methodology: Clinical and food Salmonella isolates received from the Epidemiological Surveillance Unit, Ministry of Public Health (ESUMOH) and the Lebanese Agriculture Research Institute (LARI) between 2011 and 2014 were identified to the species level using API 20E. Serotyping was carried out using the Kauffman and White scheme. Antimicrobial susceptibility to a panel of antimicrobials was tested by the disc diffusion method. The DNA fingerprinting patterns were determined using Pulsed-Field Gel Electrophoresis (PFGE) followed by BIONUMERICS analysis. Results: 290 clinical and 49 food isolates were identified to be Salmonella. The serotyping of the isolates revealed the prevalence of ten serotypes in the clinical isolates and seven serotypes within the food isolates; S. Enteritidis and S. Typhimurium being the two most common. Antimicrobial susceptibility test showed resistance to tested antimicrobials among both clinical and food isolates. PFGE results showed a wide range of pulsotypes by the different serovars. These pulsotypes were then used to confirm the linkage of two outbreaks to their food sources. Conclusion: This study calls out to set and implement food safety regulations and emphasizes the importance of surveillance through a “farm-to-fork” approach in identifying widely circulating food borne pathogens.